TRADISI PATUNG KEPALA - ICHWAN NOOR (Harmoni: Jurnal Pemikiran Pendidikan, Penelitian Ilmu-ilmu Seni, Budaya dan Pengajarannya, 2017)
In the history of culture , the artwork is the result of cultivation of the earliest discovered . In Europe in the 6000-10000 years ago are found paintings on the walls of the cave which is a handprint as impressive paintings . In Indonesia there is a cave Leang - Leang that still leaves traces of human artistic past , which is well-known in Europe was the discovery of a statue of Venus of Willendorf . This shows a desire to demonstrate to colleagues that " I've been there".The oldest theory about art starting from the beginning of Plato's 4th century BC and Aristotle in the middle of the 4th century BC that explores the theory of mimetic (mimesis = imitate ) . While the head of the oldest statues found in Egypt is the head of the statue is " Nefertiti " is made of limestone . Continues the tradition of the Roman era which have to document the faces of certain figures of his era .Head sculpture tradition changed in the modern era that emphasizes the aesthetic interest . In this era statue 's head used as reference material in the study of basic sculpture creation . In the era of modern art sculpture head start of artists Rodin and Henri Mattise , continued in the era of cubism by artist Pablo Picasso , Constantin Brancusi later artists who influenced many aspects of the shape of the primitive arts . The konstrtuktivis in Russia refers to the idea of form as something that is absolutely free from efforts reprasentasi human face andhead . Furthermore, the artist Giacometti came up with the idea surrealistik .In the pop - art culture of the 1980s creation of the statue 's head comes with a new interpretation ( more conceptual ) , which continued in the contemporary era are considered works of sculpture heads as a game , something stupid , without any findings . Climax on Hyper - realistic work of artist Ron Mueck makes a renewal of sculpture existing head .The tradition of sculpture creation as essential head , head sculpture as an interesting phenomenon in the development of the arts as a whole , which will always pull in the study with a larger context in the sociocultural kofrehensif .